Digital Health Interventions to Promote Physical Activity in Community-Dwelling Older Adults: A Systematic Review and Semiquantitative Analysis - Di Pumpo, M.; Miatton, A.; Riccardi, M. T.; Graps, E. A.; Baldo, V.; Buja, A.; Damiani, G. (International Journal of Public Health, 2025)
Objectives: Physical activity (PA) is crucial for older adults' well-being. Digital health interventions (DHIs) are important, however a synthesis aimed at healthy community-dwelling OA is lacking. This study aims to synthesize DHIs effect on PA levels among community-dwelling 60-year-old adults or older.Methods: A systematic review was performed. DHIs using eHealth/mHealth tools, apps and text messaging were included. Primary outcomes were daily steps, moderate-to-vigorous PA and sedentary time. Quality was assessed via Cochrane risk-of-bias tools. Study-reported effect, study quality, sample size, study duration and dropout rate were semiquantitatively synthesized to determine the overall category effect.Results: 12 studies were included. 75% were low-quality, sample size was 16 to 18,080, study duration was 3 to 18 weeks, average dropout rate was 4.2% to 46.7%. The synthesis of 'motivational reminders' and 'dynamic exercise programs' showed an overall positive effect, of 'PA self-monitoring' showed mixed results and 'exercise digital coaching' showed a non-positive effect.Conclusions: Motivational reminders and dynamic exercise programs proved more effective in increasing PA in older adults than other interventions and should be more embedded in structured public health programs.